The Preparation of Pre-Service Teachers for a Culture of Dignity and Peace (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
Peace education is a complex concept. Although the perception of peace always has been and continues to be in the possession of the individual, each viewpoint seems to follow a similar quest – personal dignity. The search for personal safety through the inner and outer journey for self-worth, confidence, honor, self-respect, and distinction continues in almost all individuals, communities and groups at both international and local levels. The same is equally true of our present contemporary age with its technological advancements and socio-political imbalance that set the stage for a now and me, self-indulgent generation. Understanding peace education means coming to terms with its participatory, holistic and ongoing nature.